Advancements in electron paramagnetic resonance (EPR) spectroscopy: A comprehensive tool for pharmaceutical research - Bešić Erim; Rajić Zrinka; Šakić Davor (Acta Pharmaceutica)
Electron paramagnetic resonance (EPR) spectroscopy has long been established across various scientific disciplines for characterizing organic radicals, organometallic complexes, protein structures and dynamics, polymerization processes, and radical degradation phenomena. Despite its extensive utility in these areas, EPR spectroscopy’s application within pharmaceutical science has historically been constrained, primarily due to factors such as high equipment costs, a steep learning curve, complex spectral deconvolution and analysis, and a traditional lack of emphasis on single-electron chemistry in pharmaceutical research. This review aims to provide a thorough examination of EPR spectroscopy’s applications in analyzing a wide array of para-magnetic species relevant to pharmaceutical research. We detail how EPR spectroscopy can be employed to assess free radical scavenging properties in pharmaceutical compounds, elucidate drug mechanisms of action, and explore pharmacokinetics. Additionally, we investigate the role of free radicals in drug-induced toxicity and drug-membrane interactions, while also covering the application of EPR spectroscopy in drug delivery research, advanced studies of metallodrugs, and monitoring of oxygen levels in biological systems through EPR oximetry. The recent advancements in the miniaturization of EPR spectro meters have paved the way for their application in on-site and in-line mo nitoring during the manufacturing process and quality control of pharmaceutical substances and final drug formulations due to being the only direct and non-invasive detection technique for radical detection.